Combined activity of Gracilaria edulis and Ulva reticulata on Diabetes associated Atherosclerosis: An In-vitro study - Devi. M, Devi. M; Geetha B, Geetha B (Journal of Neonatal Surgery, 2025)
Background: Diabetes-associated atherosclerosis is a complex metabolic condition driven by chronic hyperglycemia, oxidative stress, and inflammation. This study explores the therapeutic potential of hydroalcoholic extracts from two marine macroalgae, Gracilaria edulis (GE) and Ulva reticulata (UR), individually and in combination, focusing on their anti-diabetic and anti-inflammatory activities. Methods: Extracts were prepared via Soxhlet extraction and analyzed for phytochemical composition and heavy metal content. Anti-diabetic properties were assessed through alpha-amylase, alpha-glucosidase, sucrase inhibition, hemoglobin glycosylation, and yeast glucose uptake assays. Anti-inflammatory effects were examined using HRBC membrane stabilization, nitric oxide scavenging, protein denaturation, and protease inhibition assays. The extracts were tested alone and in various GE:UR ratios (1:1, 1:2, 2:1) to evaluate synergistic effects. Results: Phytochemical screening confirmed the presence of alkaloids, flavonoids, phenols, tannins, steroids, and terpenoids, with no detectable heavy metals. The 1:1 GE:UR combination exhibited the highest alpha-amylase (97.33%) and alpha-glucosidase (87.79%) inhibition. It also demonstrated strong inhibition of hemoglobin glycosylation (86.40%) and sucrase activity (82.42%). Glucose uptake was significantly enhanced (81.68%) in yeast cells. Anti-inflammatory assays showed notable results for the 1:1 combination, with high membrane stabilization (81.50%), nitric oxide scavenging (88.88%), protease inhibition (83.38%), and protein denaturation inhibition (87.89%). Conclusion: The combined extracts of Gracilaria edulis and Ulva reticulata, especially in a 1:1 ratio, exhibit potent synergistic effects against key markers of diabetes-associated atherosclerosis. These findings support their potential development as safe, natural adjunct therapies for metabolic disorders. Further in vivo and clinical investigations are warranted